Collections held by the Scottish Record Office relating to Australia and New Zealand (as filmed by the AJCP), [M584, M985-M986] - Australian Joint Copying Project; National Library of Australia; State Library of New South Wales; Scottish Record Office (Canberra : Australian Joint Copying Project, 1795)
Collection includes selected items from: Correspondence of the Kennedy Family, Earls of Cassillis; Correspondence of the Campbell Family, Earls of Breadalbane, Papers and correspondence of James and Richard D. Campbell, Papers and correspondence of Clerk Family of Penicuik, correspondence of Cunninhame Family relating to the wreck and survivors of the Amilla, Papers of Fox Maule, Secretary at War (1846-1852) and Secretary for War (1855-1858). Letters and other papers relating to the estate of Colonel Daniel Macpherson in Australia, Papers and correspondence surrounding land in Murray region of Western Australia, Documents relating to Campbell Drummond Riddell. Abstracts of accounts and bills of Major Robertson's company of the 96th Regiment in Auckland and Launceston, 1842-1844. Publications by Commissioners of Emigration concerning emigration to North American and Australian colonies including application forms, 1831-1833. Diary of Alexander Strathern on a voyage from Glasgow to Melbourne on the cargo ship Loch Tay, Oct. 1871-Jan. 1872 and on the return voyage on the Loch Tay from Melbourne to Liverpool, Mar.-Jul. 1872. Papers of the Dundas Family of Melville, including correspondents: Henry Dundas, Robert Dundas, Sir Richard Dundas, Sir John Dalrymple, Frederick Thomson, Alexander Dalrymple, Sir Hew Dalrymple, J. Gambier, Captain Archibald Duff, K. Finlay, William Loring, Admiral Sir George Seymour, Lieutenant Edward Bastard, Sir Joseph Banks, Lieutentnat G.A. Ross, Sir Samuel Auchmunty and Samuel Kekewich. Majority of the papers relate to Navy operations in the East Indies and wider pacific region as well as trade opportunities, troops and conflict in East Indies, opportunities for sea expeditions, ship building material and techniques, East India Company, appointments and promotions in civil and military service and campaign in Java, 1762-1861. Journal of Lord Elphinstone kept on his travels in Australia, New Zealand and the Pacific, Dec. 1884-Jul. 1885. Correspondence between Henry William Murray and his father John Dalrymple Murray referring to settler lifestyle, sheep farming, financial situation and goldfields, 1853-1854. Records relating to the investments and financial situation of Beatrice Bell of Mildura and Melbourne, 1920-1923. Papers of the Ogilvy Family, Earls of Seafield. The papers mainly include correspondence between Charles Grant and members of the Royal Navy during the period when he commanded HMS Seahorse and HMS Lenox, 1760-1806.
National Library of Australia holds microfilm master.
Filmed as part of the Australian Joint Copying Project by the National Library of Australia and the Library of New South Wales.
Australian Joint Copying Project handbook. Part 8 : Miscellaneous [M series]
Australian Joint Copying Project miscellaneous series M584, M985-M986.
Also available online
Microfilmed from originals held at: Scottish Record Office.
Keywords: Australia -- Emigration and immigration -- Archives; Great Britain -- Colonies -- Emigration and immigration -- Archives; Great Britain -- Colonies -- Administration -- Archives